Poverty in Malaysia Region : A Bibliometric Analysis - Abdul Hayy Haziq, Mohamad; Siti Nur Fatin Atirah, Rosli; Rossazana Ab-Rahim, Ab-Rahim; Noorhaslinda, Kulub Abd Rashid; MOHD SUFFIAN, MOHAMED ESA (Human Resource Management Academic Research Society, 2024)
This bibliometric study aims to analysis focus on the keywords "poverty" and "Malaysia" in the Scopus database from 2018 to 2023. In total, 395 documents were extracted for this study, which successfully identified all of the research questions and conducted numerous analyses on things like the yearly trend of publications, the most influential institution, the most cited author, the type of documents, the most popular journals for the same field of study, and many other things. There are four research questions in this study; (1) What is the publication trend in this research field?,(2) Which are the influential journals and research organizations dominating this research field?,(3) What is the top-cited research publications in this research field?, (4) What is the future research’s direction in this research field?. This study shows the future direction for the poverty issues in Malaysia and enlightens the area of poverty dimensional for a greater contribution.